PENGEMBANGAN MODEL PEMBELAJARAN KOLABORATIF UNTUK PENDIDIKAN SOSIOLOGI DAN ANTROPOLOGI DI ERA DIGITAL - Fritz Hotman Syahmahita Damanik (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2023)
This study aims to determine the development of a collaborative learning model for sociology and anthropology education in the digital era. The research method uses descriptive qualitative with literature study data collection techniques, in analyzing data researchers use reduction, presentation, and conclusion drawing techniques. The results showed that the collaborative learning approach in Sociology and Anthropology education in the digital era has significant implications and benefits. This model improves students' social interaction, strengthens social skills, and creates a dynamic classroom environment. In addition, students develop critical thinking skills through discussions, collaborative projects and skills-based evaluation. Technological literacy is a key focus, preparing students for the digital world and giving them flexibility in learning. The model also provides practical experience in applying sociological and anthropological concepts in real-world situations, and builds students who are ready to face complex future challenges. Despite challenges such as teacher training and access to technology, the development of this model responds to changes in education, providing a solid foundation for relevant learning and deep understanding.